L protein characterization and in silico screening of putative broad range target molecules for pathogenic mammarenaviruses from South America - Rodrigues Dutra, João Victor; Santos, Igor Andrade; Grosche, Victória Riquena [UNESP]; Jardim, Ana Carolina Gomes [UNESP]; de Aguiar, Renato Santana; Junior, Nilson Nicolau; José, Diego Pandeló (Taylor & Francis, 2024)
The genus Mammarenavirus belonging to the family Arenaviridae encompasses pathogenic viral species capable of triggering severe diseases in humans, causing concern for the health system due to the high fatality rate associated with them. Currently, there is a dearth of specific therapies against pathogens of the genus. Natural products isolated from plants have impacted the development of drugs against several diseases. The Núcleo de Bioensaios, Biossíntese e Ecofisiologia de Produtos Naturais (NuBBE) database offers several natural compounds with antimicrobial activities that can be used in the development of new antiviral drugs. In this context, here we modeled the arenavirus L protein, multifunctional machinery essential for the viral replicative cycle, making this enzyme a potential candidate for targeting the development of antivirals against genus pathogens. Using the modeled L protein, a virtual screening was performed, which suggested eleven molecules from the NuBBE database that binds to the active site of the L protein, which was promising in the in silico predictions of absorption and toxicity analysis. The NuBBE 1642 molecule proved to be the best candidate for four of the five species evaluated, acting as a possible broad-spectrum molecule. Additionally, our results showed that the L protein is highly conserved among species of the genus, as well as presenting close phylogenetic relationships between many of the species studied, strengthening its candidacy as a therapeutic target. The data presented here demonstrate that some NuBBE molecules are potential ligands for the L protein of arenaviruses, which may help to contain possible outbreaks. Communicated by Ramaswamy H. Sarma.
Keywords: L protein; Mammarenavirus; molecular docking; natural products; structural analysis